Characterization of microorganisms from Sitakunda hot spring (Chittagong University Journal of Biological Sciences, 2013)
Water, leaf, stone and sand samples from Sitakunda hot spring were studied and the microorganisms isolated from these samples were thoroughly characterized. The pH of the collected samples was found to range from 8.5 to 8.9 and the recorded temperature varied from 26.1 to 29.8 ºC during winter season. BOD of the collected water samples ranged from 10 to 92 mg/L, while COD was almost zero. The total alkalinity and chlorine content ranged from 12 to 20 mg/L and 13.9 to 18.3 gm/L respectively. Quantitative enumeration of bacterial population showed the range of 8.0×102 to 3.8×105 cfu/ml or gm sample. All the 9 selected isolates were identified as Bacillus coagulans (S1B4), Bacillus laterosporus (SB18), Bacillus megaterium (S2B11), Bacillus popilliae (S4P1), Bacillus firmus (S5B1), Citrobacter intermedius (S4B17), Listeria monocytogenes (S1B1), Listeria denitrificans (S2B) and Pseudomonas mendocina (S4P3). Bacillus laterosporus, Bacillus megaterium and Listeria denitrificans showed better growth in presence of methane gas in nutrient broth. By direct microscopic observation 7 genera of cyanobacteria (Arthrospria, Microcoleus, Oscillatoria, Schyzothrix, Scytonema, Nostoc and Gloeocapsa) and 4 genera of diatoms (Gomphonema, Melosira, Navicula and Pinnularia) were detected in the water sample DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13394 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):107-117, 2009